2016
DOI: 10.18632/oncotarget.12332
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation patterns of ABCB1, ABCC1 and ABCG2 in human cancer cell lines, multidrug-resistant cell models and tumor, tumor-adjacent and tumor-distant tissues from breast cancer patients

Abstract: Overexpression of ABCB1, ABCC1 and ABCG2 in tumor tissues is considered a major cause of limited efficacy of anticancer drugs. Gene expression of ABC transporters is regulated by multiple mechanisms, including changes in the DNA methylation status. Most of the studies published so far only report promoter methylation levels for either ABCB1 or ABCG2, and data on the methylation status for ABCC1 are scarce. Thus, we determined the promoter methylation patterns of ABCB1, ABCC1 and ABCG2 in 19 human cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
(80 reference statements)
2
30
0
Order By: Relevance
“…To analyze ABCG2 methylation, we examined 4 CpGs in a region of 360 bp in the ABCG2 promoter region. We did not observe any changes in methylation of these 4 CpGs during the development of IM-resistance, these findings are in line with those of different cancer entities, such as glioblastoma multiforme [ 50 ], breast-cancer [ 26 ] or multiple myeloma [ 51 ], where no or only partial impact of ABCG2 methylation could be observed. For ABCB1 , we did not observe changes in methylation during the development of IM-resistance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To analyze ABCG2 methylation, we examined 4 CpGs in a region of 360 bp in the ABCG2 promoter region. We did not observe any changes in methylation of these 4 CpGs during the development of IM-resistance, these findings are in line with those of different cancer entities, such as glioblastoma multiforme [ 50 ], breast-cancer [ 26 ] or multiple myeloma [ 51 ], where no or only partial impact of ABCG2 methylation could be observed. For ABCB1 , we did not observe changes in methylation during the development of IM-resistance.…”
Section: Discussionsupporting
confidence: 89%
“…In several cancer entities, aberrant ABCB1 or ABCG2 methylation was shown, i.e. in leukemia or solid tumors [ 23 25 ] and was also observed in drug-resistance [ 26 , 27 ]. In CML patients, aberrant DNA methylation of various genes could be associated to disease progression and potentially, IM-resistance [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggested that HOXA5 inhibited the progression of GC. In order to further explore the underlying mechanisms, we used RT-qPCR to detect the expression of the following genes in 30 GC tissues, including tumorigenesis-related genes ( p21, p53 and β-catenin ), proliferation-related genes ( cyclin B1, cyclin D1, c-Myc and Ki67 ), angiogenesis-related genes [vascular endothelial growth factor ( VEGF ) A, VEGFR2 and epidermal growth factor ( EGFR )], metastasis-related genes [matrix metalloproteinase ( MMP2 ) and ( MMP7 )], apoptosis-related genes ( BCL2 and caspase-3 ), EMT markers (vimentin, N-cadherin and E-cadherin), stemness markers ( Lgr5, CD44 and EpCAM ) and multi-drug resistance genes ( ABCC1, ABCG2 and Beclin1) ( 10 15 ). A Spearman's correlation model was used to examine the correlation between each of these genes and HOXA5 mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…ATP-binding cassette transporter super-family has vital effect on MDR in cancer, which is reported to a main leading cause of chemotherapeutic failure in various cancers through regulating the efflux of chemotherapeutic drugs [ 15 18 ]. Previous reports have exhibited ABCC1 to be up-regulated in colorectal cancer [ 19 ], lung cancer [ 20 ], and breast cancer [ 21 ]. MDR-1 serving as a protein scavenger also can capture and transport various chemotherapeutic agents out of cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%